Nostrum et regni nostri registrum. Srednjovjekovni arhiv Ugarsko-hrvatskog kraljevstva - Matijević-Sokol, Mirjana (2008)
Analiziraju se dokumenti koji govore o uspostavi i načinu djelovanja kraljevskog registra (registrum regale) za Ugarsku i Slavoniju pod kraljem Karlom I. oko 1330. godine i za Dalmaciju i Hrvatsku u razdoblju od 1358.-1360. poslije Zadarskog mira. Do sada nisu bile poznate činjenice iz vrela koje bi jasnije prikazivale ovu važnu ustanovu. Kraljevski registar uspostavljen je po uzoru na anžuvinsku kancelariju u Napulju, s ciljem da vodi evidenciju i zaštićuje isprave koje su izašle iz kraljevske kancelarije, a tiču se darovanja posjeda, sloboština i drugih povlastica. Uspostava kraljevskog registra pratila je reforme koje su u Ugarsko-hrvatskom kraljevstvu provodili Anžuvinci. Uz kraljevski registar, kao kompatibilna ustanova, razvila se i ojačala djelatnost vjerodostojnih mjesta (loca credibilia).
Newly discovered documents on trial of the Zaboky family contain data which confirm that the King's register for the territory of Hungary and Sclavonia (nostrum et regni nostri registrum) was established in the period of Charles I (1301-1342), in which the most important documents from the King's chancellory, concerning bestowal of properties, liberties and other mercies, were inscribed. Organization and functioning of that institution has, in Hungarian historiography, been discussed on the basis of indications. A mandate of the King Lodovic, from 1345, describes, clearly and with no doubts, the way in which register was kept. It was situated in the King's court. Documents were inscribed in a short form, but with all elements of legal act. Deeds of donation might have been renovated on the basis of existing inscriptions. Register was given to the care of vice-chancellor, with title of conservator. King’ s register for the territory of Dalmatia and Croatia was established after Zadar’ s peace, in the period from 1358 to 1360, when administrative reforms were going-on in that part of the Kingdom. Knowledge about organization and functioning of that register was possible on the ground of data from the document originating from 1370, recently discovered in Split's Chapter, which was serving to the King's commissioners while they were checking a state of matters in the field. Existence and functioning of the register influenced and strentghened a role and importance of administrative system and of loca credibilia. That is a context which allows to perceive a lifting of Dalmatian chapters into the status of loca credibilia in a new light, same as the moment when they began keeping their registers.
Projekt MZOS
Projekt MZOS
HRV